2003
DOI: 10.1093/toxsci/kfg087
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Changes in Gene Expression in Fetal Rat Testes following Exposure to Di(n-butyl) Phthalate

Abstract: Di(n-butyl) phthalate (DBP) alters male reproductive development by decreasing testicular testosterone (T) production when fetuses are exposed on gestation days (GD) 12-21. Previous studies have shown altered gene expression for enzymes in the T biosynthetic pathway following exposure to DBP. The objectives of this study were to develop a more detailed understanding of the effect of DBP on steroidogenesis, using a robust study design with increased numbers of dams and fetuses, compared with previous studies, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
121
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(136 citation statements)
references
References 47 publications
12
121
0
3
Order By: Relevance
“…It was demonstrated that when these phthalates are delivered per os to pikeperch during the sex differentiation stage, there is a delay in testis development and the feminization of the male gonads is induced (JarmoÂłowicz et al, unpublished data). Additionally, there is a link between the presence of some phthalates (including DBP) in mammals and oxidative stress caused by excess reactive oxygen species (ROS) (Barlow et al 2003, Lehmann et al 2004, Liu et al 2005. In humans, ROS can cause lipid peroxidation in sperm cell membranes, changes in the structure of membrane receptors, and in enzyme and transport proteins, and it can also increase anomalies in chromatin structure and breaks in sperm DNA strands (Hughes et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that when these phthalates are delivered per os to pikeperch during the sex differentiation stage, there is a delay in testis development and the feminization of the male gonads is induced (JarmoÂłowicz et al, unpublished data). Additionally, there is a link between the presence of some phthalates (including DBP) in mammals and oxidative stress caused by excess reactive oxygen species (ROS) (Barlow et al 2003, Lehmann et al 2004, Liu et al 2005. In humans, ROS can cause lipid peroxidation in sperm cell membranes, changes in the structure of membrane receptors, and in enzyme and transport proteins, and it can also increase anomalies in chromatin structure and breaks in sperm DNA strands (Hughes et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…A number of endocrine disrupting chemicals (EDCs), including DBP, are known to be anti-androgenic ). The androgenic effects of DBP include decrease in testosterone synthesis possibly due to reductions in the expression of genes involved in cholesterol transport and downstream synthesis (Barlow et al, 2003) or include the inhibition of the expression of a number of key enzymes involved in cholesterol uptake or transport and steroidogenesis (Stocco, 2001;Stocco et al, 2005) with downstream reproductive consequences.…”
Section: Effects On Steroidogenic Enzyme Genesmentioning
confidence: 99%
“…Consequently, intermediate stages of crowing development could be associated with reduced testosterone production stemming from social stimulation (Groothuis). Several reports (Gray et al, 1982;Barlow et al, 2003) have indicated that testosterone effects on germinal tissue are in fact, responsible for the observed decrease in seminiferous tubular height and the corresponding decrease in testis weight. In this present study, there was no difference between the mean body weight and testicular weight.…”
Section: Effects On Histopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Following from this, in the field of DOHaD it is common to sample only a few offspring per litter, with the assumption that the findings from these individuals are representative of the characteristics of their littermates (Haseman and Hogan, 1975). However, there is an increasing body of evidence to suggest that there is greater intra-litter variability than inter-litter variability in fetal outcomes following many prenatal exposures (van der Schoot, 1992; Howdeshell and Saal, 2000; Barlow et al, 2003;Godin et al, 2010;Kietzman et al, 2014;Han et al, 2016).…”
Section: Rationale For the Use Of Individual Animals As Experimentalmentioning
confidence: 99%